Epitaxial growth of highly compressively strained GeSn alloys up to 12.5% Sn - Oehme, Michael; Buca, Dan; Kostecki, K.; Wirths, S.; Hollaender, B.; Kasper, E.; Schulze, J. (Journal of Crystal Growth, 2013)
This paper reports on the growth and characterization of highly compressive strained GeSn layers on thin strain relaxed Ge virtual substrates on Si wafers. Sn concentration up to 12.5%, which is about more than 10 times the thermal equilibrium predicted for GeSn binaries, are successfully epitaxially grown by ultra-low temperature (160 C) molecular beam epitaxy. A minimum channeling yield of 9% evidence the high crystalline quality of the GeSn alloys while angular channeling scan demonstrate that all GeSn layers are fully pseudomorphic on the relaxed Ge virtual substrate. The strain analysis shows a deviation from the Vegard's law for Sn contents above 8%. The analysis is completed by the Raman mode dependence on the alloys composition. © 2013 Published by Elsevier B.V.
CRIS-Team Scopus Importer:2021-06-29
Keywords: A3. Molecularbeamepitaxy; B3. Heterojunctionsemiconductordevices